2019
DOI: 10.1002/bjs.10962
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of liver transplantation in patients with colorectal metastases confined to the liver

Abstract: Background Patients with non‐resectable colorectal metastases are currently treated with chemotherapy. However, liver transplantation can increase the 5‐year survival rate from 9 to 56 per cent if the cancer is confined to the liver. The aim of this study was to estimate the cost‐effectiveness of liver transplantation for colorectal liver metastases. Methods A Markov model with a lifetime perspective was developed to estimate the life‐years, quality‐adjusted life‐years (QALYs), direct healthcare costs and cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Resource allocation and utilization is also a relevant aspect to consider in this discussion. It has been shown by our group that LT of colorectal liver metastases is a reasonable and cost effective treatment in high income countries when selecting "low risk" patients (9). Furthermore, we have also reported that the transplanted patients sustain good quality of life after LT except for the first 3 post-transplant months.…”
supporting
confidence: 62%
“…Resource allocation and utilization is also a relevant aspect to consider in this discussion. It has been shown by our group that LT of colorectal liver metastases is a reasonable and cost effective treatment in high income countries when selecting "low risk" patients (9). Furthermore, we have also reported that the transplanted patients sustain good quality of life after LT except for the first 3 post-transplant months.…”
supporting
confidence: 62%
“…We have previously shown that patients in the SECA-I trial who received LT had good quality of life up to 3 years after LT . Furthermore, LT is cost-effective compared with the cost of modern oncologic treatments . The major obstacles for being able to offer patients with CRC an LT internationally is the scarcity of donor grafts.…”
Section: Discussionmentioning
confidence: 99%
“…125 The cost-effectiveness of LT for CRLM in highly selected patients was recently shown. 126 Definitive confirmation of these retrospective findings will hopefully come from several ongoing trials. The SECA-III trial (NCT03494946) will compare LT to best multimodal alternative treatment (chemotherapy +/-locoregional therapies).…”
Section: Lt For Unresectable Crlm: a New Hopementioning
confidence: 84%